The Influence of Social Media Marketing and Influencer Endorsement on the Purchase Decision of Le Minerale Bottled Water Products in Generation Z with Trust as a Moderating Variable - Muhamad Roisul Muttaqin (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
The rapid development of information technology has driven the transformation of conventional marketing strategies into digital ones. This study aims to analyze the influence of Social Media Marketing (SMM) and Influencer Endorsement on the purchase decision of Le Minerale Bottled Water products among Generation Z in Semarang Regency, as well as to test the role of Trust as a moderating variable. This type of research is quantitative, using a survey method with a Google Form-based questionnaire. The research sample was determined to be 140 Generation Z respondents residing in Semarang Regency, selected through a purposive sampling technique. The analysis tool used was the IBM SPSS Statistics 25 program with a Moderated Regression Analysis (MRA) approach. The results of the first-stage linear analysis showed that partially, SMM (X_1) has a positive and significant effect on the purchase decision (Y) with a significance value of 0.000. Influencer Endorsement (X_2) also has a positive and significant effect on the purchase decision with a significance value of 0.007. However, the results of the second-stage MRA test proved that the Trust variable (M) is not capable of moderating the relationship between either SMM or Influencer Endorsement and consumer purchase decisions (the interaction significance values are 0.994 and 0.910, respectively). Trust in this study acts as a pure predictor variable (predictor moderator) that directly exerts a strong impact on the purchase decision loyalty of Generation Z.